PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Melindawati, Silfi; Rahma Yirlanda, Nalpi (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This study was motivated by several issues: the LKPD content did not meet learning objectives, it did not use any instructional model, and the illustrations lacked color, reducing students’ interest. The aim of this research is to develop and validate an LKPD based on the Cooperative Integrated Reading and Composition (CIRC) model. This is a research and development (R&D) study using the 4-D model, which includes define, design, develop, and disseminate stages. Due to the Covid-19 pandemic, the study was limited to small-scale dissemination. Validation results from three experts indicated a very high level of validity: design scored 3.71, language 3.16, and content 3.81 (all categorized as very valid). Practicality tests showed scores of 93.7% from teachers and 91.6% from students (very practical). Effectiveness scores were 95.31% for PB 1 and 95.75% for PB 2 (very effective). Therefore, the CIRC-based LKPD is highly valid, practical, and effective for use in fourth-grade integrated thematic learning